2018
DOI: 10.3340/jkns.2017.0238
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Stereotactic Radiosurgery for Recurred Metastatic Brain Tumors

Abstract: ObjectiveWe investigated the outcomes of repeat stereotactic radiosurgery (SRS) for metastatic brain tumors that locally recurred despite previous SRS, focusing on the tumor control. MethodsA total of 114 patients with 176 locally recurring metastatic brain tumors underwent repeat SRS after previous SRS. The mean age was 59.4 years (range, 33 to 85), and there were 68 male and 46 female patients. The primary cancer types were non-small cell lung cancer (n=67), small cell lung cancer (n=12), gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…However, both low tumour volume and high-prescription radiation dose were significantly related to the tumour control following repeat SRS for these tumours after previous SRS, which is a general understanding of primary SRS for metastatic brain tumours. 53 In asymptomatic patients, a systemic therapy approach, based on the BC subtype, might be preferred. In the absence of cerebral symptomatology, the urgency is to systemic control and the best treatment for brain metastasis remains the treatment of cancer.…”
Section: Current Treatment Options For Bmbcmentioning
confidence: 99%
“…However, both low tumour volume and high-prescription radiation dose were significantly related to the tumour control following repeat SRS for these tumours after previous SRS, which is a general understanding of primary SRS for metastatic brain tumours. 53 In asymptomatic patients, a systemic therapy approach, based on the BC subtype, might be preferred. In the absence of cerebral symptomatology, the urgency is to systemic control and the best treatment for brain metastasis remains the treatment of cancer.…”
Section: Current Treatment Options For Bmbcmentioning
confidence: 99%
“…Among them, 22 were excluded due to a lack of prior SRS/SRT to the target metastasis (previous WBRT only or mixed interventions) or insufficient data reporting [ 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A total of 13 studies met the inclusion criteria and were analyzed in the final meta-analysis [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. They included 464 patients and 549 treated metastases with a median follow-up of 11 (1–124) months by pooling patients from the 11 studies for which this data was available.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the risk of bias for missing data, only four studies had short or unreported data, leading to a moderate level of risk. For the remaining articles reviewed, the level of risk was considered low because of the application of an adequate follow-up schedule with sufficient time to assess the efficacy and toxicity of radiation therapy [ 51 , 53 , 56 , 60 ]. Nevertheless, no study reported analytical strategies to account for loss of information.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two full-text papers were initially included out of 1136 potential references after check for duplicate or pertinence. Among them, 21 were excluded due to lack of prior SRS to the target metastasis (previous WBRT only, or first stereotactic irradiation of the target lesion after prior SRS to another intracranial site, or mixed interventions) or insufficient data reporting (Guan et al (2019); Maranzano et al, 2019;Kim et al, 2018;Koiso et al, 2016;Huang et al, 2017;Shen et al, 2016;Bates et al, 2016;Yomo and Hayashi, 2016;Shultz et al, 2015;Monaco et al, 2014;Kurtz et al, 2014;Kim et al, 2013;Maranzano et al, 2012;Kwon et al, 2007a;Shuto et al, 2004;Hillard et al, 2003;Wowra et al, 2002;Bhatnagar et al, 2002;Noël et al, 2001;Davey et al, 1994;Kwon et al, 2007b). Hence, eleven studies were considered eligible for data extraction and included in the final meta-analysis (Iorio-Morin et al, 2019;Dincoglan et al, 2019;Moreau et al, 2018;Balermpas et al, 2018;Rana et al, 2017;McKay et al, 2017;Minniti et al, 2016;Greto et al, 2014;Terakedis et al, 2014;Holt et al, 2015;Koffer et al, 2020), accounting for 335 patients and 389 treated metastases.…”
Section: Resultsmentioning
confidence: 99%